The Role of Community Health Workers in the Control and Management of Leprosy: A Scoping Review - Srihartati, Enik; Dewi, Arlina (National Journal of Community Medicine, 2025)
Introduction: Leprosy remains a persistent public health challenge in many endemic regions, exacerbated by delayed diagnosis and sociocultural stigma. Community Health Workers (CHWs) have emerged as pivotal actors in promoting early detection, treatment adherence, and stigma reduction. Methods: This scoping review synthesizes current evidence on CHW-led leprosy interventions, drawing from articles published in PubMed, Scopus, and Google Scholar between 2000 and 2025. A total of 23 studies from countries including India, Brazil, and Indonesia were included. Data were extracted and analyzed thematically to explore CHW roles, early detection methods, and challenges encountered. Results: CHWs were involved in activities such as door-to-door screening, household contact tracing, community education, and rehabilitative support. Their contributions were associated with reduced diagnostic delays and improved community engagement. However, most studies did not isolate the specific impact of CHWs, limiting causal attribution. Common barriers included inconsistent training, competing responsibilities, weak referral systems, and insufficient funding and policy support. Conclusion: CHWs play a multifaceted role in enhancing leprosy control, but their effectiveness is constrained by systemic and contextual barriers. Future research should adopt more rigorous study designs, including Community-Based Participatory Research (CBPR), to better assess CHW-specific contributions and cost-effectiveness. Strengthening training, supervision, and intersectoral collaboration is essential to maximize the impact of CHW-led interventions.